2020
DOI: 10.3390/pharmaceutics12070682
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Potential Ocular Mucoadhesive Nano Lipid Carriers Using Full Factorial Design

Abstract: Generally, topically applied eye drops have low bioavailability due to short residence time and low penetration of the drug. The aim of the present study was to incorporate dexamethasone (DXM) into nano lipid carriers (NLC), which contain mucoadhesive polymer, in order to increase the bioavailability of the drug. A 23 factorial experimental design was applied, in which the three factors were the polymer, the DXM, and the emulsifier concentrations. The samples were analyzed for particle size, zeta potential, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…The mucoadhesive behavior of DEX-loaded NLCs was demonstrated for porcine cornea by Kiss et al, both with and without the use of cationic polymer coating, while Liu et al demonstrated similar effects using coumarin-6 loaded NLCs on rabbit corneas [ 18 , 57 ]. In the latter study, a slight increase in retention of chitosan-coated NLCs was observed, postulated to be due to the ability of chitosan to form an interpenetration layer with the mucosal layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mucoadhesive behavior of DEX-loaded NLCs was demonstrated for porcine cornea by Kiss et al, both with and without the use of cationic polymer coating, while Liu et al demonstrated similar effects using coumarin-6 loaded NLCs on rabbit corneas [ 18 , 57 ]. In the latter study, a slight increase in retention of chitosan-coated NLCs was observed, postulated to be due to the ability of chitosan to form an interpenetration layer with the mucosal layer.…”
Section: Resultsmentioning
confidence: 99%
“…In the current study cholesterol-Labrafac™ lipophile-based nanostructured lipid carriers (CHLF-NLCs) were prepared to encapsulate dexamethasone. Given the widespread applicability of DEX as a therapeutic, it has been investigated for use by a number of researchers for incorporation into NLCS [ 18 , 19 , 20 ]. Considering the extensive research already carried out on the optimization of both NLCs and DEX-NLCs, in the present study, the focus is instead placed on the potential translation of NLC technologies and assessment at pilot scale production.…”
Section: Introductionmentioning
confidence: 99%
“…The best formulation significantly improved dexamethasone solubility and ensured a high corneal retention of the drug when tested ex vivo. Based on this promising data, the same research group proposed, in a successive publication [ 114 ], similar NLC functionalised with a mucoadhesive polymer (hydroxypropyl methylcellulose) that could improve nanoparticle adhesion to the mucosal surface. Two further responses related to nanoparticle population distribution by volume were included in a three-factor, two-level full factorial design that led to eight unique formulations ( Table 1 ).…”
Section: Optimising the Outcomes: Statistical Design Of Experiments (Doe)mentioning
confidence: 99%
“…These polymers can be associated with lipid nanoparticles to improve the residence time of the particles in the precorneal area, enhancing drug penetration across epithelia [82,119]. Most widely used polymers are hydroxypropyl methyl cellulose [120], polyvinyl alcohol [121], sodium hyaluronate [122], chitosan [123]. As an example of application of these systems, F. Wang et al prepared SLNs loaded methazolamide coated with chitosan for the treatment of glaucoma [124].…”
Section: Bioadhesive Polymersmentioning
confidence: 99%